2013
DOI: 10.1021/jf400697r
|View full text |Cite
|
Sign up to set email alerts
|

Relative Bioavailability of Tropical Volcanic Soil-Bound Chlordecone in Piglets

Abstract: The application of chlordecone (CLD), a chlorinated polycyclic ketone pesticide, until 1993 in the French West Indies has resulted in long-term pollution of agricultural soils (10% of them exceed 1 mg kg(-1)). The aim of this study was to assess the impact of two tropical volcanic soils, an andosol and a nitisol, on CLD availability in piglets, using the relative bioavailability (RBA) approach. For both soils and relative to an oil matrix, RBA was close to 100%, indicating that CLD was not retained in the soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…These differences between both organs are consistent with previous observations in rodent [28], lambs [8], pigs [9] and humans [29]. This particular affinity of CLD to liver could be explained by non-clearly identified proteins which readily bound CLD [30].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These differences between both organs are consistent with previous observations in rodent [28], lambs [8], pigs [9] and humans [29]. This particular affinity of CLD to liver could be explained by non-clearly identified proteins which readily bound CLD [30].…”
Section: Resultssupporting
confidence: 90%
“…CLD-transfer to lambs [8], piglets [9] and laying hens [10] have been proven to not be limited by the type and properties of Antillean soils (nitisol or andosol). The specific efficiency of this transfer is related to the availability of this pesticide for outdoor reared animals.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison between oil-fed and soil-fed animals groups was realized in order to assess exposure to spiked soil with OM in terms of exposure via the alimentary one. Similar methodology was previously used [19] [21] . The present study provides RBA estimates using a single dose comprised in a linearity-tested range of doses [17] .…”
Section: Methodsmentioning
confidence: 96%
“…This extended rearing duration exposes them to an absolute soil intake higher than for NRES animals. Based on literature (Bouveret et al, 2013;Jurjanz et al, 2014) soil intake by animals observed during our experiment would result in CLD contamination when the animals would have grazed on polluted areas.…”
Section: Soil Intakementioning
confidence: 94%
“…Therefore, the exposure of free range animals to pollutants is closely linked to the amount of soil ingested which can be particularly high for some ruminants, up to 14% of the daily dry matter intake (DMI) in cattle (Fries et al, 1982), and up to 30% of DMI in sheep (Thornton and Abrahams, 1983) reported on pastures in very extensive temperate systems. Several authors reported that soil-bound persistent organic pollutants such as polychlorinated biphenyls in lactating goats and piglets (Delannoy et al, 2015), but also for chlordecone (CLD) in piglets (Bouveret et al, 2013) and growing lambs (Jurjanz et al, 2014) are highly bioavailable and fully absorbed in the digestive tract. Consequently, an accurate quantification of soil intake is required to evaluate the risk for food safety.…”
Section: Introductionmentioning
confidence: 99%